(untitled) (Applied Biological Research, 2011)
Apple (Malus domestica Borkh.), a predominant fruit crop of Jammu & Kashmir State, is grown on an area of 1,19,041 ha and contributes towards 65% of the total fruit produce of the State (Anonymous, 2008). In recent years apple trees have encountered a new problem in the form of various types of cankers which have assumed epiphytotic proportions in some pockets of Kashmir valley (Bhat et al., 2009). The cankers inflict huge economic losses through girdling of limbs and branches, blightening and die-back of twigs and ultimately lead to the death of either whole or part of the tree (Jones and Aldwinkle, 1990). In view of the alarming damage by canker diseases on apple trees, a preliminary study was undertaken to assess the canker status in Kashmir valley and to identify the causal pathogen.